Conceptions and practices of embracement to the family members in psychosocial attention in alcohol and other drugs - Gabrielle Leite Pacheco Lisbôa; Mércia Zeviani Brêda; Maria Cícera dos Santos de Albuquerque (Rev Rene)
This is a qualitative research made from March 2012 to February 2014 to identify and to analyze conceptions and practices of embracement to the family members of the people who use drugs, from the family’s and the professionals’ perspective in a Psychosocial Attention Center specialized in Alcohol and Other Drugs in Maceió, AL, Brazil. Data collection was made by semi-structured interviews with the use of previously elaborated script. Bardin's thematic analysis and discussion approved by Merhy revealed it as an act of receiving. For professionals, it is an administrative reception, triage, and transfer of information. For the family members, it is always to be welcome. The practice, present in relations in which there is the encounter professional-user, materialized in family groups and listening. In the working process, embracement to the families expresses the need of qualified listening, constitution of bond and their co-responsibilities.